Cost‐related medication nonadherence among adolescent and young adult cancer survivors. Issue 14 (23rd May 2017) - Kaul, Sapna; Avila, Jaqueline C.; Mehta, Hemalkumar B.; Rodriguez, Ana M.; Kuo, Yong‐Fang; Kirchhoff, Anne C.
Abstract : BACKGROUND: This study investigated cost‐related medication nonadherence among survivors of adolescent and young adult cancer and a comparison group in the United States. METHODS: A cross‐sectional analysis of the 2013 to 2015 National Health Interview Survey was performed. N=953 patients who were diagnosed with cancer between the ages of 15 and 39 years were identified, and a comparison group was created using propensity scores. Cost‐related medication nonadherence was determined by individuals' report of skipping medication, taking less medication, or delaying filling medication to save money in the previous year. Covariates included demographics, insurance status, financial factors (eg, out‐of‐pocket health care expenditures), and health‐related factors (eg, comorbidity and mental distress). Chi‐square tests were used to compare nonadherence between survivors and the comparison group. Logistic regressions identified covariates associated with nonadherence. RESULTS: Survivors were more likely to report nonadherence than the comparison group (23.8% vs 14.3%; P  < .001). Survivors were also more likely to report that they could not afford medication, asked their physician for lower cost medication, and used alternative therapies in the previous year to save money. Uninsured survivors were more likely to report nonadherence than those privately insured (odds ratio [OR], 3.19; 95% confidence interval [CI], 1.67‐6.09). Non‐Hispanic black survivors, those who reported greater mental distress, and those with greater comorbidities reported nonadherence more often than their counterparts. Survivors reporting a usual source of care were at a lower risk of nonadherence than those without it (OR, 0.39; 95% CI, 0.18‐0.82). CONCLUSIONS: Cost‐related communication with survivors may be needed to increase medication adherence. Uninsured and sicker survivors should receive regular screening to improve adherence. Future work should evaluate adherence for specific drugs. Cancer 2017;123:2726‐34 . © 2017 American Cancer Society . Abstract : Close to a quarter of survivors of adolescent and young adult cancer report medication nonadherence, whereas only 14% in a comparison group do. Uninsured survivors (vs privately insured survivors) and those without a usual source of care (vs those with a usual source of care) face a greater risk of medication nonadherence.